Answer:
13.70
Step-by-step explanation:
a^2+b^2=c^2
a = side 1
b = side 2
c = hypotenuse
9.2^2 + b^2 = 16.5^2
272.25 - 84.64 = 187.61 =b^2
√187.61 = b = 13.697 = 13.70
The Population mean is 3.3 and the Sample mean is 3.6, 3.6-3.3 is 0.3
Answer:
(5x+1)(x+7)
Step-by-step explanation:
4x^2+26x+6+x^2+10x
5x^2+36x+7
(5x+1)(x+7)
Prove
5x*x + 5x*7 + 1*x + 1*7
= 5x^2 + 35x + x + 7
= 5x^2 + 36x + 7
Answer:
- <u><em>A dilation by a scale factor of 4 and then a reflection across the x-axis </em></u>
Explanation:
<u>1. Vertices of triangle FGH:</u>
- F: (-2,1)
- G: (-3,3)
- H: (0,1)
<u>2. Vertices of triangle F'G'H':</u>
- F': (-8,-4)
- G': (-12,-12)
- H': (0, -4)
<u>3. Solution:</u>
Look at the coordinates of the point H and H': to transform (0,1) to (0,-4) you can muliply each coordinate by 4 and then change the y-coordinate from 4 to -4. That is<em> a dilation by a scale factor of 4 and a reflection across the x-axis.</em> This is the proof:
- Rule for a dilation by a scale factor of 4: (x,y) → 4(x,y)
(0,1) → 4(0,1) = (0,4)
- Rule for a reflection across the x-axis:{ (x,y) → (x, -y)
(0,4) → (0,-4)
Verfiy the transformations of the other vertices with the same rule:
- Dilation by a scale factor of 4: multiply each coordinate by 4
4(-2,1) → (-8,4)
4(-3,3) → (-12,12)
- Relfection across the x-axis: keep the x-coordinate and negate the y-coordinate
(-8,4) → (-8,-4) ⇒ F'
(-12,12) → (-12,-12) ⇒ G'
Therefore, the three points follow the rules for <em>a dilation by a scale factor of 4 and then a reflection across the x-axis.</em>
Answer: 5 players on each team
Step-by-step explanation:
5+7+8= 4/20